Managing Road-blocks Psychologically For Self-Driving Vehicles - Samal, Sarat K (International Journal of Psychosocial Rehabilitation, 2019)
Self-driving cars promise a bright future, but only if it is feasible for the public to solve the social obstacles that stand in the way of widespread acceptance. Widespread autonomous vehicle adoption promises to make us healthier, safer and more effective. Manufacturers are flying through the remaining technical challenges to the preparation of the vehicles. But the largest roadblocks in the path of mass adaption may be psychological, not technical; 75 percent of Americans report fearing riding in an autonomous vehicle, with only 18 percent indicates that trust on the vehicle will be established. Experts explore three elements: legal dilemmas, crash overreactions and the complexity of the decision-making systems of the vehicles-and suggest steps to address them. It will be necessary to address both the social and ethical dilemmas in order to earn public trust. And because it always seemed unlikely that regulators will implement the most stringent self-protective solution - in which autonomous vehicles would never harm the passengers, no matter how small the danger to passengers and high the risk to others - users will have to confront the fear of consumers that the car might one day decide to harm them.